Affective engineering: What is it actually? - Aziz, Fakhrul Anuar; Husni, Husniza; Jamaludin, Zulikha (2010)
Current scenarios in product design are stepping from functional towards emotional appeal of users.Emotional aspect is seen crucial in product design to ensure user acceptance and thus the successfulness of the product.The base of affective engineering concerns the approach for consideration of design elements that map the feeling of users. This paper introduces and discusses affective engineering in terms of its definition, underlying theory, and methods. Affective engineering, strongly related to interaction design or IxD, supports in the elicitation of user requirements and specification as well as design and development of a product.In order to understand affective engineering better, this paper presents an example of design innovation of a blog layout, which is user-focused.It is promising that affective engineering can be used for designing satisfying user-focused product.